EFFECTIVE TECHNIQUES FOR TEACHING BASIC GRAMMAR - Qaxramonova Sevinch Abdulla qizi, (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Annotation: Teaching basic grammar is one of the most important components of foreign language education, particularly for elementary learners who are developing the foundation of their communicative competence. Grammar provides the structural framework  that  allows  learners  to  construct  meaningful  sentences,  convey  ideas effectively, and engage in authentic communication. Traditional grammar instruction often focuses on memorization of rules and isolated exercises, which can leave learners unable to use grammar practically and may reduce motivation. This article examines effective techniques for teaching basic grammar, including contextualized instruction, guided discovery, and communicative practice. By integrating Uzbekistan’s national educational  standards  with  internationally  recognized  methodological  principles,  it highlights  ways  to  make  grammar  learning  both  comprehensible  and  functional, ensuring learners develop both knowledge and practical skills [1, 12–18].